31 'I Like Palliative Care Now': Improving confidence in palliative care using simulation for foundation year 2 trainees. (14th March 2023) - Massey, Laura; Robinson, Lucy; Huggin, Amy; Churm, Deepta
Abstract : Background: Simulation as a learning platform is recognised internationally as beneficial in terms of education, training and assessment of doctors. This study aimed to introduce and evaluate a novel Palliative Medicine simulation session as a tool for Foundation Year 2 (FY2) doctors to gain competency and confidence in the assessment and management of life-limiting illness. Prior to the session only 27% of FY2s felt that their training so far had prepared them to deal with Palliative Care (PC) issues as Higher Trainees. Methods: We designed the PC simulation session based on the FY2 curriculum. The three scenarios involved management of opioid toxicity, breaking bad news and shared decision making with a role-play patient with a gastrointestinal bleed. Session faculty included a mix of healthcare professionals, but always included a PC specialist. We evaluated the session using a pre and post-session questionnaire collecting data using 5-point Likert scales and free-text comments. We calculated percentage agreement with questionnaire statements using Likert scores of 4 or 5 and compared candidate's answers pre and post-session. We analysed qualitative data using content analysis. Researcher and methodological triangulation increased the credibility of the findings. Results: 95.6% of FY2s felt the session addressed the challenges they experienced managing PC issues. The percentage of candidates who felt confident in PC management and communication increased post session in all domains measured. The content analysis found that the commonest issue FY2s worried about was communication followed by prognostication. The 'debrief' was the most commonly cited positive aspect of the session. Suggestions for improvement included prescribing practice and use of professional role-players. Conclusion: Our session was effective at improving confidence in the management of PC patients for FY2s. The content analysis shows learners particularly valued the simulation and debrief format. The evaluation supported integrating the session long-term into local foundation teaching.